Implementation of Augmented Reality for Introducing Nutritious Food to Elementary School Children Using the Marker-Based Tracking Method - Budi Arifitama; Putri Nugrahayati; Silvester Dian Handy Permana (Justek : Jurnal Sains dan Teknologi, 2025)
Pre-adolescence is a vital stage of human development, where proper nutrition significantly influences growth and long-term productivity. As children often consume snacks both at home and in school environments, ensuring they have access to safe and nutritious food is essential. This research aims to develop an educational tool to introduce healthy and balanced food choices to children using augmented reality (AR) technology. The study employs a marker-based tracking method, a widely used technique in AR development, to display interactive 3D visualizations of nutritious food items. This method was selected for its ability to provide fast and accurate marker recognition, making it highly suitable for educational use. Experimental testing demonstrated that the application effectively rendered stable and well-positioned 3D objects at a tracking distance of 10–30 cm. As a result, the AR-based learning tool successfully enhanced children's ability to recognize and understand different types of nutritious foods. The findings suggest that augmented reality, particularly through marker-based tracking, can effectively increase engagement and support nutrition education among school-aged children.